3D‐Printed Light‐Driven Microswimmer with Built‐In Micromotors. Issue 1 (1st September 2021) - Chen, Yin; Yang, Huanhua; Li, Mingliang; Zhu, Shilu; Chen, Shuo; Dong, Liuyi; Niu, Fuzhou; Yang, Runhuai
Abstract: Untethered biocompatible microswimmers driven by micromotors in fluids can enable innovative technologies in fields such as biology and chemical and biomedical engineering. However, efficiently driving and controlling the movement of microswimmers by light remains a challenge. Herein, a method for fabricating a light‐driven microswimmer with built‐in micromotors and 3D‐printed multiscale features that exhibits high photocatalytic performance is proposed. TiO2 ‐CaCO3 composite microparticles (TC) are fabricated as highly efficient micromotors that provide high photocatalytic efficiency in bubble generation, while 3D‐printed hydrogels are fabricated as TiO2 ‐CaCO3 /PEGDA (TC/P) microswimmers that provide biocompatibility, large specific surface area, and controllable movement. The results show that TC micromotors produced by physical mixing at a specific concentration exhibit a large specific surface area, reduced agglomeration, increased photocatalytic active sites, and improved photocatalytic stability. TC micromotors are effectively loaded into the porous hydrogel by 3D printing for multiscale fabrication to improve the photocatalytic performance across scales and realize effective and directional driving under violet light excitation. The TC/P microswimmers exhibit stable catalysis and motion in 7 days, at which point the catalysis by TiO2 is already ineffective. With stability, biocompatibility, and biomedical functions, this multiscale fabricated microswimmer exhibits great potential in micromanipulation and targeted therapy. Abstract : A method for multiscale fabrication of visible light‐driven, untethered, 3D printable, biocompatible, and stable microswimmers is proposed. Highly efficient micromotors are fabricated to provide high photocatalytic efficiency in bubble generation, while 3D‐printed PEGDA hydrogels are fabricated as microswimmers that provide biocompatibility, large specific surface area, and controllable movement for biomedical applications.